Demonstrativo da produção de resíduos orgânicos e recicláveis do município de Erechim – RS - Pasuch, Ariane Tanise (2015)
To know the reality of the waste produced by cities is fundamental to think the development, education and public politics articulated with other social segments. This work has as objectives to demonstrate the evolution in the production of organic waste and recyclable the city of Erechim, RS in the last 4 years. Organize the data concerning the collecting of organic materials and recyclable of this city, quantitatively demonstrate the material coming from conventional collecting . The data were obtained from the Department of the Environment of Erechim - RS, reporting the reality of waste collected, grounded and sold by six associations of collectors of the city. It can be perceived that there was an expressive increase in the year 2013 with approximately 15% in relation to 2012, but slightly less than 0.5% for 2014, if it is designed by the end of 2015, has the same increase media. Materials are classified for sale as follows: water, olive oil, crystal, milk, white paper, paper, cardboard, HDPE (high density polyethylene), PET (Polyethylene Terephthalate) white, mixed green PET, PET, mixed PET PEAD, thin plastic, plastic bag, scrap metal, glass. It can be noticed that the materials of greater representativeness in quantity, have low commercial value, such as the mixed cardboard and paper. Note also, a reduced quote to your Pet. The delivery of the collected material is divided by the associations that are closest to the neighborhood of collecting, depending on the size of the pavilion, the quantity of gatherers and office hour in which they work. There is still an association that performs the screening in sanitary landfill and receives all the organic load, around eight to ten daily, besides the collected by outsourced company sweeping, which covers the public dumps of sightseeing. All pavilions of screening have environmental license, the associations are legally established, the sanitary landfill is a municipal and licensed by the state body competent authority. Human activities generate waste, some of easy destination other nor both. The management of these leftovers is of shared responsibility, whereby the entire collectivity thinking and manage their offcuts, rethinking their way of living and consequences, production and waste.